2014
DOI: 10.1111/aos.12407
|View full text |Cite
|
Sign up to set email alerts
|

Time evolution of active caspase‐3 labelling after in vivo exposure to UVR‐300 nm

Abstract: ABSTRACT.Purpose: To determine the time evolution of active caspase-3 protein expression in albino rat lens after in vivo exposure to low-dose UVR-300 nm, as detected by immunofluorescence. Methods: Forty Sprague-Dawley rats were unilaterally exposed in vivo to 1 kJ/ m 2 UVR-300 nm for 15 min. At 0.5, 8, 16 and 24 hr after the UVR exposure, the exposed and contralateral nonexposed lenses were removed and processed for immunohistochemistry. Three mid-sagittal sections from each lens were stained. The cells labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Ayala et al showed that double threshold dose of 8 kJ/m 2 of UVR-B increases mRNA and protein expression of both p53 and caspase 3 in the rat lens epithelium 7 d after exposure [18]. Moreover, a recent study in our group concluded that expression of active caspase 3 protein increases with a peak of 16 h after exposure to sub-threshold dose of 1 kJ/m 2 of UVR-B [19]. Galichanin et al investigated the time evolution of GADD45α, TP53 and CASP3 gene expression in the rat lens after in vivo exposure to double threshold dose of 8 kJ/m 2 of UVR-B [20].…”
Section: Introductionmentioning
confidence: 70%
“…Ayala et al showed that double threshold dose of 8 kJ/m 2 of UVR-B increases mRNA and protein expression of both p53 and caspase 3 in the rat lens epithelium 7 d after exposure [18]. Moreover, a recent study in our group concluded that expression of active caspase 3 protein increases with a peak of 16 h after exposure to sub-threshold dose of 1 kJ/m 2 of UVR-B [19]. Galichanin et al investigated the time evolution of GADD45α, TP53 and CASP3 gene expression in the rat lens after in vivo exposure to double threshold dose of 8 kJ/m 2 of UVR-B [20].…”
Section: Introductionmentioning
confidence: 70%
“…UV light has been shown to cause apoptosis in lens cells and in whole lenses (21,22,(27)(28)(29) and because UV light exposure is associated with cataract formation (18 -20), we sought to determine the effect of UVA light on the subunits of the integrin ␣V␤5 receptor and on the process of lens cell phagocytosis of apoptotic debris. To test this, human SRA 01/04 lens epithelial cells were exposed to UVA light using a UVA LED array.…”
Section: Uva Treatment Of Lens Epithelial Cells Results In Loss Of Bomentioning
confidence: 99%
“…Most of the UV light transmitted to the lens is therefore UVA light; this is primarily absorbed by the anterior lens epithelium, and long term UVA exposure is believed to contribute to lens damage (24,83,84). UV light exposure of lens epithelial cells is associated with apoptosis of lens epithelial cells (21,22,(27)(28)(29) and human cataract formation (18 -20); however, the mechanisms used by lens epithelial cells to deal with the downstream effects of UV light and other insults, i.e. apoptosis and accumulation of apoptotic debris to ensure epithelial cell homeostasis and lens transparency, remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rat was unilaterally exposed to UVR-300 nm as described elsewhere (16). After the exposure, both lenses were extracted and prepared for immunofluorescence detection of active caspase-3 as described above (Sample preparation).…”
Section: Application Of the Automatic Algorithmmentioning
confidence: 99%